Investigation on the flow field characteristics of composite insulators under extreme wind loads. (November 2021) - Qian, Tian; Zhanshan, Xie; Weidong, Shi; Zhouhao, Shi; Tan, Linwei
Highlights: A double row line vortex is formed behind the mandrel, the turbulent kinetic energy and dissipation rate of the windward side of the mandrel sheath are the largest. The shed structure of composite insulator results in the uneven pressure distribution between the sheds. The high-speed flow in the horizontal direction directly impacts the lower surface of the V-string composite insulator shed WIAD, which will form a vortex, and induce the pressure fluctuation of sheds. Abstract: In order to investigate the internal causes of fatigue failure of composite insulators under extreme wind loads. In this paper, the numerical model of FXBW-500/300 composite insulator(CI) is constructed firstly. Based on RNG k-ε turbulence model, the flow field of single side of V-string, flow field between large and small sheds of suspension string composite insulation and near flow field of whole insulator were carried out. The results show that the change of circumferential pressure and turbulent kinetic energy at the junction of shed and mandrel of CI is the largest, and the stress concentration is easy to occur at the junction of shed and core rod. Meanwhile, the suspension CI is better than the V-string CI in the variation amplitude of wind pressure and turbulence of flow field near the shed.